Quality of life assessment in patients on chronic dialysis: Comparison between haemodialysis and peritoneal dialysis at a national hospital in Vietnam. Issue 2 (2nd January 2022) - Tran, Phuong Que; Nguyen, Nhi Truc Y; Nguyen, Bach; Bui, Quynh Thi Huong
Abstract: Objectives: End‐stage renal disease (ESRD) is a chronic disease that can adversely affect the patient's quality of life (QoL) in terms of functional limitation and cognitive impairment. This study aimed to identify the factors associated with QoL in patients with ESRD undergoing dialysis at a national hospital in Vietnam. Methods: A descriptive cross‐sectional study was conducted among outpatients aged ≥18 years who underwent haemodialysis (HD) or peritoneal dialysis (PD) for at least 3 months at Thong Nhat Hospital, Ho Chi Minh City, Vietnam from May 2020 to July 2021. QoL was measured using the validated Vietnamese version of the EuroQol‐5 Dimensional‐5 Level (EQ‐5D‐5L). The factors associated with the QoL of patients with ESRD undergoing dialysis were identified using multiple linear regression analysis. Results: In total, 131 (73.6%) and 47 (26.4%) patients underwent HD and PD, respectively. Overall, 178 (55.6%) patients were men (median age, 66 [56–79] years). The mean EQ‐5D‐5L score was significantly higher in patients undergoing PD than in those undergoing HD (0.848 ± 0.183 vs. 0.766 ± 0.231; p = 0.030). Older age (β = −0.006; p < 0.001) and peptic ulcer disease (β = −0.083; p = 0.029) were associated with lower QoL scores. PD treatment was associated with higher QoL scores (β = 0.065; p = 0.046). Conclusions: It is necessary to improve the QoL of patients undergoing dialysis, especially of elderly patients and patients with peptic ulcer disease. PD may be a better method for maintenance dialysis, if applicable, in terms of QoL.